1992
DOI: 10.1104/pp.100.3.1442
|View full text |Cite
|
Sign up to set email alerts
|

Photophysiology of the Elongated Internode (ein) Mutant of Brassica rapa

Abstract: Several phytochrome-controlled processes have been examined in etiolated and light-grown seedlings of a normal genotype and the elongated internode (ein/ein) mutant of rapid-cycling Brassica rapa. Although etiolated ein seedlings displayed normal sensitivity to prolonged far-red light with respect to inhibition of hypocotyl elongation, expansion of cotyledons, and synthesis of anthocyanin, they displayed reduced sensitivity to prolonged red light for all three of these deetiolation responses. In contrast to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 28 publications
(31 reference statements)
3
59
1
Order By: Relevance
“…each photoreceptor, although few data are available to test the conservation of gene function in seed plants other than Arabidopsis. Nonetheless, the available data from Brassica, cucumber (Cucumis sativus), pea (Pisum sativum), tobacco (Nicotiana tabacum), tomato (Solanum lycopersicum), maize (Zea mays), and rice (Oryza sativa) suggest that the functions of phyA and phyB are generally conserved and were established prior to the split of eudicots and monocots (Ballaré et al, 1991;Childs et al, 1991;Devlin et al, 1992;Weller et al, 2004;Sheehan et al, 2007;Takano et al, 2005Takano et al, , 2009, although independently duplicated phyB may subdivide functions differently than is seen in Arabidopsis phyB and phyD (e.g., Hudson et al, 1997;Kerckhoffs et al, 1999;Weller et al, 2000;Sheehan et al, 2007). Functional data from dicots that diverge deeper than the eudicot/monocot split in the angiosperm phylogenetic tree are needed to infer that their functions are conserved in all angiosperms, but this is a reasonable hypothesis.…”
Section: Conservation Of Phya and Phyb Functionmentioning
confidence: 99%
“…each photoreceptor, although few data are available to test the conservation of gene function in seed plants other than Arabidopsis. Nonetheless, the available data from Brassica, cucumber (Cucumis sativus), pea (Pisum sativum), tobacco (Nicotiana tabacum), tomato (Solanum lycopersicum), maize (Zea mays), and rice (Oryza sativa) suggest that the functions of phyA and phyB are generally conserved and were established prior to the split of eudicots and monocots (Ballaré et al, 1991;Childs et al, 1991;Devlin et al, 1992;Weller et al, 2004;Sheehan et al, 2007;Takano et al, 2005Takano et al, , 2009, although independently duplicated phyB may subdivide functions differently than is seen in Arabidopsis phyB and phyD (e.g., Hudson et al, 1997;Kerckhoffs et al, 1999;Weller et al, 2000;Sheehan et al, 2007). Functional data from dicots that diverge deeper than the eudicot/monocot split in the angiosperm phylogenetic tree are needed to infer that their functions are conserved in all angiosperms, but this is a reasonable hypothesis.…”
Section: Conservation Of Phya and Phyb Functionmentioning
confidence: 99%
“…Previous work has shown that low R:FR light can induce shade avoidance phenotypes in the Wisconsin Fast Plants (WFP) variety of rapid-cycling B. rapa (Devlin et al, 1992(Devlin et al, , 1997. We find that this is a general attribute of B. rapa varieties: seedlings of an inbred line of B. rapa subsp.…”
mentioning
confidence: 99%
“…Elongated plants are more susceptible to physical damage (Morinaka et al, 2006), and shade responses may diminish the allocation of photosynthate and other growth resources to harvested tissues (Ballare et al, 1997). Brassica rapa and other species of the Brassica genus are important vegetable and oilseed crops, which in low R:FR light display phyB-dependent SAS phenotypes (Devlin et al, 1992(Devlin et al, , 1997. The recent sequencing of the B. rapa genome (Wang et al, 2011), its close relationship with the well-studied model plant Arabidopsis, its economic value, a large seedling size amenable to spatial studies, and the availability of mutants and rapidcycling varieties (Williams and Hill, 1986;Stephenson et al, 2010) make this an attractive model system for the study of shade avoidance.…”
mentioning
confidence: 99%
“…However, there was a slight (but insignificant) increase in BMDR-1, which may reflect the increased phytochrome levels in BMDR-1 relative to BMDR-8. The phyB null mutants in other plant species displayed an elongated growth pattern, had reduced chlorophyll content, and lacked a deetiolation response to highirradiance R (Childs et al, 1991(Childs et al, , 1992Devlin et al, 1992;Lopez-Juez et al, 1992;Reed et al, 1993). BMDR-1 did not lack a deetiolation response to high-irradiance R and it was not visibly less green.…”
Section: Discussionmentioning
confidence: 99%
“…The increased level of spectrophotometrically detectable total phytochrome was found to be largely accounted for by an increase in phyA (Principe et al, 1992), but nothing was known about the regulation of phyB levels. The hy3 mutant in Arabidopsis , the ma 3 R mutant in sorghum (Childs et al, 1992), the ein mutant in Brassica rapa (Devlin et al, 1992), and the lh mutant in cucumber (Lopez-Juez et al, 1992) all flower early and lack a light-stable phyB protein. In Arabidopsis and sorghum it has been shown that the mutation is located in the PHYB gene Childs et al, 1997).…”
mentioning
confidence: 99%